An evaluation of retention and marginal seating of Ni-Cr alloy cast restorations using three different luting cements: An in vitro study - Bikash K Pattanaik; S J Nagda (Wolters Kluwer Medknow Publications, 2012)
Context: Clinical and laboratory studies regarding performance of recently introduced luting cements: Adhesive resin cement and resin-modified glass ionomer cement (GIC), are limited. Aims: To compare the retention and marginal seating of Ni-Cr alloy restorations using newer luting cements: Resin-modified GIC and adhesive resin cement with those of the oldest cement, zinc phosphate. Materials and Methods: Thirty maxillary premolars of similar sizes were prepared to receive cast metal copings. Copings were placed on the prepared teeth and the marginal opening was examined using a Nikon Measuroscope. The specimens were randomly assigned to three groups. Group I castings were luted with zinc phosphate, Group II castings luted with resin-modified GIC, and Group III castings luted with adhesive resin cement. After cementation marginal seating was measured. Tensile loads required to dislodge the crowns were obtained using MTS machine. Statistical Analysis Used: Tukey's test, Analysis of Variance (ANOVA). Results: For zinc phosphate cement, mean marginal seating was 31 microns. Mean retentive strength was 287 Newtons. For resin-modified GIC, mean marginal seating was 29.6 microns. Mean retentive strength was 610 Newtons. For adhesive resin cement, mean marginal seating was 49 microns. Mean retentive strength was 613 Newtons. Conclusions: Marginal seating of adhesive resin cement was significantly greater than that of zinc phosphate and resin-modified GIC. Retentive strength of adhesive resin cement and resin-modified GIC was significantly greater than that of zinc phosphate There was no significant difference of retentive strength between adhesive resin cement and resin-modified GIC.